Source material for food gatherers and hunters to accompany the course of study in industrial arts - grades one to four. Part I-Tropical peoples. Part II-Eskimos. - School District of Philadelphia, Pa. Board of Public Education. (Philadelphia, 1937)
Mode of access: Internet.